Mass spectrometry imaging for biosolids characterization to assess ecological or health risks before reuse - Villette, Claire; Maurer, Loïc; Zumsteg, Julie; Mutterer, Jérôme; Wanko, Adrien; Heintz, Dimitri (Nature communications, 2023)
Biosolids are byproducts of wastewater treatment. With the increasing global population, the amounts of wastewater to be treated are expanding, along with the amounts of biosolids generated. The reuse of biosolids is now accepted for diversified applications in fields such as agriculture, engineering, agro-forestry. However, biosolids are known to be potential carriers of compounds that can be toxic to living beings or alter the environment. Therefore, biosolid reuse is subject to regulations, mandatory analyses are performed on heavy metals, persistent organic pollutants or pathogens. Conventional methods for the analysis of heavy metals and persistent organic pollutants are demanding, lengthy, and sometimes unsafe. Here, we propose mass spectrometry imaging as a faster and safer method using small amounts of material to monitor heavy metals and persistent organic pollutants in different types of biosolids, allowing for ecological and health risk assessment before reuse. Our methodology can be extended to other soil-like matrices. Mass spectrometry imaging is a suitable tool for the analysis of non-cohesive materials. Here, authors show that it can be used to detect persistent organic pollutants (POPs) and heavy metals (HMs) in biosolids using small amounts of material with speed and safety.